Knowledge and Risk Factors of Intraepithelial Lesion amongst Women of Childbearing Age in Jos, Nigeria - Y. Selji; J. O. Adisa; S. M. Gamde; K. I. Bali; M. S. Udo; C. A. Ikeh (Journal of Applied Sciences and Environmental Management)
Cervical cancer is a major public health issue worldwide, particularly in low- and middle-income countries. Persistent infection with human papilloma virus (HPV) has been implicated in causing cervical cancer through sexual contact. Therefore, the objective of this paper is to investigate the Knowledge and Risk Factors of Intraepithelial Lesion amongst Women of Childbearing Age in Jos, Nigeria using one hundred women in a detailed questionnaire administration.  Data obtained show that 35% of women had cervical intraepithelial lesions, with 57.2% classified as high-grade squamous intraepithelial lesions (HSIL), 31.4% as low-grade squamous intraepithelial lesions (LSIL), and 11.4% as other non-premalignant lesions. Only 30% of women were knowledgeable about cervical cancer and its risk factors. The study reveals a rather high HSIL prevalence of cervical intraepithelial lesions among these women had inadequate knowledge of cervical cancer, indicating a need for increased awareness efforts to reduce the burden of cervical cancer. Implementing comprehensive prevention and control measures, including HPV vaccination, and access to timely treatment, is crucial to reducing the burden of cervical cancer and improving women's health worldwide.